A critique of Paulo Freire's perspective on human nature to inform the construction of theoretical underpinnings for research. (20th April 2020) - Sanders, Kate
Abstract: This article presents a critique of Paulo Freire's philosophical perspective on human nature in the context of a doctoral research study to explore "muchness" or nurses' subjective experience of well‐being; and demonstrates how this critique has informed the refinement of the theoretical principles used to inform research methodology and methods. Engaging in philosophical groundwork is essential for research coherence and integrity. Through this groundwork, largely informed by Freire's critical pedagogy and his ideas on humanization, I recognized the need to clarify my understanding of the concepts of persons and personhood and how this related to Freire's use of the term human beings. This clarification process is essential to ensure congruence between the theoretical principles that I draw from his work and my beliefs about persons, personhood and person‐centredness. The article begins with a brief introduction to the research, followed by an overview of Freire's philosophical perspectives, and subsequently, the critique process is presented and discussed. This process involved engaging with the vast literature and debates about what it means to be a person, to make sense of the often complex and contradictory arguments. Eventually, three headings emerged that helped me to frame my evolving understanding: Our species: human beings ; The kind that we are: human nature ; and This person that I am: personhood. Through this process of exploration, I recognized that Freire's perspective on human nature (a) foregrounded cognitive rationality, which presented itself as a limitation when considering my ontological beliefs and the focus of my research, leading me to draw on the work of Mark Johnson and his ideas about embodiment to help me to further develop my theoretical principles; (b) focused on the "collective" rather than individuals, which is a shortcoming in relation to person‐centred research that acknowledges the uniqueness of participants.